Homes, Home Lives and Precarious Privilege: Older Western Residents and Differing Lifestyle Mobilities in Ubud, Bali. Issue 2 (3rd April 2023) - Green, Paul
ABSTRACT: This article explores later-life subjectivities and experiences of precarious privilege through the ethnographic lens of home life and the material culture of homes. Based on long-term fieldwork with older white foreigners in Ubud, Bali, I examine the role of building projects and vernacular architecture in forging moral connections across self, local culture and place-myth. These subject positions of belonging and identity are nourished yet unsettled by the growing presence of younger foreigners and modern housing forms in Ubud. I argue that experiences of privilege and precarity coexist and evolve across time, in places such as Bali that are transformed by lifestyle mobilities and tourism development. A focus on home lives and the materiality of homes hones analysis of precarious privilege towards understandings of belonging and place attachment. If distinctions between traditional homes and modern villas confirm differences within lifestyle 'communities', they also speak to spatialised entanglements of global and localised political economy dynamics that disrupt the privileged home lives and identity projects of ageing mobile subjects. For Western residents in Ubud, my analysis shows, precarious privilege takes the form of rising costs of living, property insecurity, a fear of crime, and uneven relationships with local domestic workers, landowners and landlords.